A Stab in the Dark? Point-of-Care Testing in the Population With Hip Fracture. (September 2015) - Dawkins, Claire; Atkinson, Kate; Tate, Anne; Eardley, W. G. P.
Hip fracture incidence rises globally in an aging population who live in an era of financial austerity. Health service providers are under pressure both to optimize care and to increase efficiencies in the management of this vulnerable patient group. One area of inefficiency in perioperative processes is the assessment of deranged clotting profiles secondary to warfarinization and in the monitoring of hemoglobin. Delays are inherent in these processes, threatening patient care and impacting on financial incentivisation of performance. Point-of-care testing, while widespread in other areas of health care, is underutilized in hip fracture management. This work explores the application to hip fracture care of this technology and suggests future direction to investigate its potential benefits.